Does it pay to delay social security?*. (April 2014) - SHOVEN, JOHN B.; SLAVOV, SITA NATARAJ
Abstract Social Security benefits may be commenced at any time between ages 62 and 70. As individuals who claim later can, on average, expect to receive benefits for a shorter period, an actuarial adjustment is made to the monthly benefit to reflect the age at which benefits are claimed. We investigate the actuarial fairness of that adjustment in light of recent improvements in mortality and historically low interest rates. We show that delaying is actuarially advantageous for a large number of people, even for individuals with mortality rates that are twice the average. At real interest rates closer to their historical average, singles with mortality that is substantially greater than average do not benefit from delay, although primary earners with high mortality can still improve the present value of the household's benefits through delay. We also investigate the extent to which the actuarial advantage of delay has grown since the early 1960s, when the choice of when to claim first became available, and we decompose this growth into three effects: (1) the effect of changes in Social Security's rules, (2) the effect of changes in the real interest rate, and (3) the effect of changes in life expectancy. Finally, we quantify the extent to which the gains from delay can be expected to increase in the future as a result of mortality improvements.